Tindak Pidana Penganiayaan Yang Mengakibatkan Matinya Seseorang (Studi Kasus Putusan Nomor: 24/Pid.B/2013/PN.Sp) - I Kadek Agus Irawan; I Nyoman Sujana; I Ketut Sukadana (Jurnal Analogi Hukum, 2019)
Persecution is a savage act carried out by someone to hurt others both physically and mentally. The phenomenon of the many acts of persecution that occurred in the community was motivated by several things including the economic situation of the perpetrators, the psychiatrists who were not stable, how the perpetrators were raised in the family. From these problems several problems were formulated, among others: criminal persecution, 2. What criminal sentence was handed down by the judge against the alleged persecution that resulted in someone's death. In writing this essay using normative research methods, using a legal, conceptual and case approach. From the legal research that has been done, it can be concluded that, the judge's judgment in punishing the perpetrator is juridical, then the consideration based on evidence and consideration is non-judicial, the sentence imposed by the panel of judges on the accused of torture which results in a maximum sentence seven years stipulated in article 351 paragraph 3 of the Criminal Code.